Assessment of the Antigenotoxic Activity of Poly(D,L-lactic-co-glycolic acid) Nanoparticles Loaded with Caffeic Acid Phenethyl Ester Using the Ames Saimonella/Microsome Assay - Arasoglu, Tuilin; Derman, Serap (AMER CHEMICAL SOC, 2018)
In the present study, the antigenotoxic activity of poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) loaded with caffeic acid phenethyl ester (CAPE) was investigated in comparison to free CAPE using the Ames Salmonella/ microsome assay. Additionally, to elucidate the impacts of the type of solvent effect on antigenotoxic activity, the following systems were tested: CAPE in water (poor solvent), ethyl alcohol (good solvent), and PLGA NPs (unknown). The effect of the NP system on solubility was investigated for the first time by assessing the antigenotoxic potential. In this study, the CAPE/PLGA NPs were synthesized using an oil-in-water (o/w) single-emulsion solvent evaporation method with an average size of 206.2 +/- 1.2 nm, zeta potential of -19.8 +/- 2.5 mV, encapsulation efficiency of 87.2 +/- 2.5%, and drug loading of 53.3 +/- 1.8%. According to the results of the antigenotoxic activity, the highest antimutagenic activity in both applied strains was found for CAPE in ethanol, and the lowest activity was detected for CAPE in water. Our study has shown that NP systems exhibit high antigenotoxic activity, which is similar to the results of CAPE dissolved in ethanol. These results have shown that NP systems increase biological activity of hydrophobic substances by increasing their solubility and that the use of PLGA instead of organic solvents in drug production may provide an increase in their medical utility.
Keywords: caffeic acid phenethyl ester; poly(D,L-lactic-co-glycolic acid); PLGA; nanoparticle; antigenotoxicity activity; Ames; ANTICANCER ACTIVITY; PLGA NANOPARTICLES; INFLAMMATION; ENHANCEMENT; QUERCETIN; EXTRACTS; VULGARE; Agriculture; Chemistry; Food Science & Technology